Dilemmas in general theory of planning: with the introduction of Bob Jessop - Rittel, Horst W. J.; Webber, Melvin M. (Journal of Public Governance, 2014)
Th esearch for scientific bases for confronting problems of social policy is bound to fail, because of the naturę of these problems. They are “wicked” problems, whereas science has developed to deal with “tame” problems. Policy problems cannot be defmitively described. Moreover, in a pluralistic society there is nothing like the undisputable public good; there is no objective definition of eąuity; policies that respond to social problems cannot be meaningfully correct or false; and it makes no sense to talk about “optimal solutions” to social problems unless severe ąualifications are imposed first. Even worse, there are no „solutions” in the sense of defłnitive and objective answers.